SISTEM PAKAR DIAGNOSA PENYAKIT TELINGA HIDUNG TENGGOROK (THT) DENGAN MENGGUNAKAN METODE INFERENSI BERBASIS SHORT MESSAGE SERVICE (SMS) - Indriyawati, Henny; Sugiharto, Aris; Surarso, Bayu (Universitas Diponegoro, 2013)
Public understanding about otolaryng desease (THT) is still insufficient. Most of them medically untrained so that when they experienced thesymptoms of the disease, they might not be able to understand how to overcome the symptoms. It is regrettable when the symptoms could not be handled because of insufficient knowledge. This problem has encouraged the birth of expert system concept. The purpose of the use of the expert system is to help public solve their problems by using the knowledge possessed by the expert system without visiting the experts directly. By the exixtence of this expert system, public are able to detect the presence of the otolaryng disease based on their symptoms. The testing of the system show that the system is capable to diagnose otolaring disease by entering a list of symptoms through short message service. Then the application will process the input data bu using inferensi method and forward chaining reasoning techniques to produce usefull information for the public. The research is result the accuracy level around 87,5%. Keywords : Expert system; Forward chaining; SMS.